A Coconut Mite, Aceria guerreronis Keifer (Arachnida: Acari: Eriophyidae) - F. W. Howard; Dave Moore (EDIS)
EENY-398, a 7-page illustrated fact sheet by F. W. Howard and Dave Moore, describes one of the worst arthropod pests of coconut palms, which attacks the young fruits and can cause scarring and distortion and premature fruit drop.  Includes sections on distribution, description, biology and ecology, hosts, damage and economic importance, detection, management, and selected references. Published by the UF Department of Entomology and Nematology, December 2006.